Pulp reaction to a tri-cure resin-modified glass ionomer - (:unkn) unknown (Mosby Inc., 1998)
Objective. This study evaluated the pulp response to a tri-cure resin-modified glass ionomer cement and compared this response to those elicited by a zinc oxide-eugenol cement and a silicate cement. Materials were placed in nonexposed class V cavity preparations on human teeth. Study Design. Sixty premolars were selected in orthodontic patients in a voluntary group of teenagers. All cavities were prepared according to International Dental Federation specifications. Resin-modified glass ionomer and silicate applications were carried out according to the manufacturers' instructions. Result. All teeth were asymptomatic. Pulp responses to the resin-modified glass ionomer cement were slightly greater than to the zinc-oxide-eugenol cement. Bacterial staining attempts were inconclusive with regard to time intervals and pulp responses. No necrotic pulps were seen in any teeth. Conclusion. The tri-cure resin-modified glass ionomer cement elicited a slightly greater adverse pulp response than did the zincoxide-eugenol cement with respect to the healing process of the pulp.